Expression, purification and functional characterization of recombinant Zucchini yellow mosaic virus HC-Pro - Füllgrabe, Marc W.; Boonrod, Kajohn; Jamous, Rana; Moser, Mirko; Shiboleth, Yoel; Krczal, Gabi; Wassenegger, Michael (Protein expression and purification, 2011)
HC-Pro is a helper component-proteinase which acts as a multifunctional protein in the potyviral life cycle. Apart from its proteolytic activity, HC-Pro has the capacity to bind duplex small RNAs (sRNAs). To investigate HC-Pro-mediated sRNA binding in vitro, high amounts of purified protein are required. For this purpose, the Zucchini yellow mosaic virus (ZYMV) HC-Pro was expressed as a fusion with hexa-histidine (6xHis) or maltose-binding protein (MBP) in Escherichia coli. The expressed fusion proteins were purified by affinity chromatography. 6xHis:HC-Pro and MBP:HC-Pro were partially soluble. Electrophoretic mobility-shift assays demonstrated that only MBP:HC-Pro exhibits the sRNA binding activity. The recombinant HC-Pro bound 21bp siRNAs as well as 19bp and 24bp siRNAs. A point mutation in the highly conserved FRNK box produced the HC-ProFINK protein, previously shown to be associated with reduced viral symptoms and weak sRNA binding. In this study, sRNA binding of the MBP:HA-HC-ProFINK was not detectable. The high yield of purified HC-Pro offers the possibility to study the biochemistry of the protein in detail.